2021
DOI: 10.3389/fvets.2020.610240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Canine and Feline Adipose-Derived Mesenchymal Stem Cells/Medicinal Signaling Cells With Regard to Cell Surface Marker Expression, Viability, Proliferation, and Differentiation Potential

Abstract: Remarkable immunomodulatory abilities of mesenchymal stem cells, also called multipotent mesenchymal stromal cells or medicinal signaling cells (MSCs), have entailed significant advances in veterinary regenerative medicine in recent years. Despite positive outcomes from MSC therapies in various diseases in dogs and cats, differences in MSC characteristics between small animal veterinary patients are not well-known. We performed a comparative study of cells' surface marker expression, viability, proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…In the present study, newly derived cAD-MSCs exhibited fibroblast-like shapes, culture-plate-adhesion capacity, and trilineage differentiation, which were similar to characteristics of human MSCs [ 14 , 15 , 18 ]. Besides, cAD-MSCs in our study had CD44 and CD90 expression of more than 95% but were deprived of CD34 and MHC class II expression, similar to a number of the previous reports [ 19 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, newly derived cAD-MSCs exhibited fibroblast-like shapes, culture-plate-adhesion capacity, and trilineage differentiation, which were similar to characteristics of human MSCs [ 14 , 15 , 18 ]. Besides, cAD-MSCs in our study had CD44 and CD90 expression of more than 95% but were deprived of CD34 and MHC class II expression, similar to a number of the previous reports [ 19 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The logarithmic growth phase cells were assessed by calculating the cell doubling time and counting using a hemocytometer. 23 All cells were suspended and then frozen in a solution containing 10% dimethyl sulfoxide (MP Biomedicals, Santa Ana, California) and 90% PBS. The cell suspension was aliquoted into sterile plastic cryo-vials, and the date, passage number, and freezing serial number were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the authors also demonstrated that umbilical cord blood MSCs showed no adipogenic differentiation abilities compared to those from the bone marrow and adipose tissue [97]. Several studies including our own have demonstrated that indeed, adipose-derived MSCs can undergo multi-lineage differentiation under different conditions [9,[98][99][100].…”
Section: Heterogeneity Of Mscsmentioning
confidence: 99%